2011
DOI: 10.1177/0748233711399319
|View full text |Cite
|
Sign up to set email alerts
|

The influence of hydrocarbon composition and exposure conditions on jet fuel-induced immunotoxicity

Abstract: Chronic jet fuel exposure could be detrimental to the health and well-being of exposed personnel, adversely affect their work performance and predispose these individuals to increased incidences of infectious disease, cancer and autoimmune disorders. Short-term (7 day) JP-8 jet fuel exposure has been shown to cause lung injury and immune dysfunction. Physiological alterations can be influenced not only by jet fuel exposure concentration (absolute amount), but also are dependent on the type of exposure (aerosol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…As indicated previously, the NRC suggested that the exposure levels in the Harris et al studies were likely higher than reported (National Research Council, 2003), and this has since been confirmed by the Harris lab (Hilgaertner et al, 2011). The report by Hilgaertner et al (2011) demonstrates JP-8-related immunosuppressive effects, including decreased spleen and thymus weights at exposure levels ≥1000 mg/m 3 and reduced IFN- γ production at doses ≥4000 mg/m 3 .…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…As indicated previously, the NRC suggested that the exposure levels in the Harris et al studies were likely higher than reported (National Research Council, 2003), and this has since been confirmed by the Harris lab (Hilgaertner et al, 2011). The report by Hilgaertner et al (2011) demonstrates JP-8-related immunosuppressive effects, including decreased spleen and thymus weights at exposure levels ≥1000 mg/m 3 and reduced IFN- γ production at doses ≥4000 mg/m 3 .…”
Section: Discussionsupporting
confidence: 51%
“…The report by Hilgaertner et al (2011) demonstrates JP-8-related immunosuppressive effects, including decreased spleen and thymus weights at exposure levels ≥1000 mg/m 3 and reduced IFN- γ production at doses ≥4000 mg/m 3 . Hilgaertner et al (2011) also indicated that these exposures were equivalent to aerosol exposures of 125 and 500 mg/m 3 in the early reports by Harris et al (1997, 2000a, 2000b, 2002, 2007, 2008). These results, which contrast with those in the present study evaluating the base jet fuel kerosene, suggest the possibility that the additives, and not the jet fuel kerosene, are primarily responsible for the immunosuppressive effects of JP-8 jet fuel.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Previous studies with hydrocarbons have shown following direct exposure toxicological effects such as adverse effects in lung ventilatory function [17], immune dysfunction [18, 25], increased tumor formation [26], and suppressed immune response to viral infections [27]. In the current study, the F1 generation animals of jet fuel lineage showed an increase in the incidence of adult-onset disease/abnormalities including prostate disease, kidney disease, ovarian primordial follicle loss, polycystic ovarian disease, pubertal abnormalities, and an overall increase in total and multiple disease/abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…In animal models low toxicity of JP-8 has been reported to cause slight dermal irritation, weak dermal sensitization, respiratory tract sensory irritation, hearing loss, nephropathy, and immunosuppressive and neurobehavioral effects [24]. Previous studies have also shown adverse effects in lung ventilatory function [17], immune dysfunction [18, 25], increased tumor formation [26] and suppressed immune response to viral infections [27]. There are no reports regarding potential epigenetic transgenerational inheritance of disease from JP-8 exposed gestating females.…”
Section: Introductionmentioning
confidence: 99%